2019
DOI: 10.32479/irmm.8025
|View full text |Cite
|
Sign up to set email alerts
|

The Model of Employee Performance

Abstract: The purpose of this study was to determine the leadership style, motivation, work discipline and employee performance at PT. Trakindo Utama Pontianak and the influence of leadership, motivation and work discipline styles on employee performance both simultaneously and partially. The research method used is survey research method. The type of data/information used is primary data with data collection techniques by observation, questionnaire and literature study. The research population is all employees of PT. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 5 publications
0
20
1
5
Order By: Relevance
“…Hia & Siregar (2019) , Nguyen et al (2020 , Sukmawati et al (2018) , Makambe & Moeng (2020) , Aeni & Kuswanto (2021) , Oyetunji et al (2019) , Primary (2022) , Lee et al (2019) , Sari et al (2021) . However, the results of this study are different from Hermina & Yosepha (2019), Lubis et al (2019), Rompas et al (2018), andWuryani et al (2021). The right leadership style can encourage employees to participate together in carrying out the work so that organizational goals can be achieved together.…”
Section: A Hypothesis 1 (Effect Of Leadership Style On Employee Perfo...contrasting
confidence: 99%
See 1 more Smart Citation
“…Hia & Siregar (2019) , Nguyen et al (2020 , Sukmawati et al (2018) , Makambe & Moeng (2020) , Aeni & Kuswanto (2021) , Oyetunji et al (2019) , Primary (2022) , Lee et al (2019) , Sari et al (2021) . However, the results of this study are different from Hermina & Yosepha (2019), Lubis et al (2019), Rompas et al (2018), andWuryani et al (2021). The right leadership style can encourage employees to participate together in carrying out the work so that organizational goals can be achieved together.…”
Section: A Hypothesis 1 (Effect Of Leadership Style On Employee Perfo...contrasting
confidence: 99%
“…Several previous studies have shown that work motivation has a positive effect on employee performance (Gunawan, 2021;Hia & Siregar, 2019;Nguyen et al, 2020;Pebrianti & Simajuntak, 2020). However, several previous studies showed different results which concluded that motivation did not affect employee performance (Hermina & Yosepha, 2019;Ismawati et al, 2018;Lubis et al, 2019;Rahmi et al, 2020;Rosalia et al, 2020).…”
Section: Introductionmentioning
confidence: 97%
“…Other studies show that TL has a high enough effect on EP when compared to instrumental leadership even though this difference is very slight (Chammas & Hernandez, 2019). EP is strongly influenced by leadership style also evidenced by Hermina and Yosepha (2019) in their research conducted at PT. Trakindo Utama Pontianak, The results showed that the TL style had a direct effect on EP.…”
Section: The Effect Of Transformational Leadership (Tl)mentioning
confidence: 81%
“…Human resource units play an important role in employee career development not only for the company's success but also for employees (Hermina & Yosepha, 2019). On the other hand, Mangkunegara (2002) mentioned some characteristics of the employee who have high performance will indicate responsibility, comprehensive work plan, trying to reach the goal, and have careful preparation.…”
Section: Resultsmentioning
confidence: 99%